The effects of delayed mandatory retirement on elderly and youth employment - Joseph Han (Korea Development Institute (KDI), 2020)
The phased implementation of the minimum mandatory retirement age (60) from 2016 has expanded the employment of older workers (55-60) but reduced that of young workers (15-29). The negative effect has been particularly pronounced at large companies or firms with a previously low official retirement age. - A difference-in-difference analysis at the establishment level reveals that a 1 person increase in those who could potentially stay owing to the new mandatory retirement age leads to a 0.6 person increase in older workers and a 0.2 person decrease in young workers. - The decline in youth employment was marked at establishments with 100+ employees or those whose retirement age was 55 or below before the statutory change. These results imply that a gradual approach is required to minimize the negative impact of delayed mandatory retirement, and that additional labor market policies are needed particularly for older workers whose employment is not protected. - Increasing the mandatory retirement age is necessary given the rapidly aging population, but the negative impact on employment can only be minimized if it proceeds slowly and in phases. - Employment services tailored to older workers should be provided, particularly for those whose retirement age is not guaranteed, and legal standards need to be improved to facilitate the creation of jobs with flexible hours.
Keywords: 330